2012
DOI: 10.1182/blood-2011-12-399667
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag inhibits the proliferation of leukemia cells via reduction of intracellular iron and induction of differentiation

Abstract: Eltrombopag (EP) is a small-molecule, nonpeptide thrombopoietin receptor (TPO-R) agonist that has been approved recently for the treatment of thrombocytopenia in patients with chronic immune thrombocytopenic purpura. Prior studies have shown that EP stimulates megakaryopoiesis in BM cells from patients with acute myeloid leukemia and myelodysplastic syndrome, and the results also suggested that it may inhibit leukemia cell growth. In the present study, we studied the effects of EP on leukemia cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
124
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 37 publications
12
124
1
1
Order By: Relevance
“…There are other publications that do not find a pro-leukemic effect [96]. In more recent MDS studies, TRAs had no effect on the rate of leukemic transformations [97].…”
Section: Tras -Side Effectsmentioning
confidence: 88%
“…There are other publications that do not find a pro-leukemic effect [96]. In more recent MDS studies, TRAs had no effect on the rate of leukemic transformations [97].…”
Section: Tras -Side Effectsmentioning
confidence: 88%
“…48 On the other hand, recent studies concluded that eltrombopag allowed the formation of normal megakaryocytic colonies without the stimulation of malignant blasts from AML and MDS patients, and also had a strong anti-leukemic effect. 37,49 Interestingly, this effect was independent of c-Mpl, but was instead mediated through the modulation of intracellular iron content. 49 Finally, Kalota et al demonstrated that eltrombopag dramatically decreases ROS levels, leading to a disruption of AML intracellular metabolism and rapid cell death.…”
mentioning
confidence: 99%
“…37,49 Interestingly, this effect was independent of c-Mpl, but was instead mediated through the modulation of intracellular iron content. 49 Finally, Kalota et al demonstrated that eltrombopag dramatically decreases ROS levels, leading to a disruption of AML intracellular metabolism and rapid cell death. 50 Thus, conflicting results were obtained concerning the potential leukemogenic effect of thrombopoietin mimetics, and further studies are required to clarify this important issue.…”
mentioning
confidence: 99%
“…3 However, in contrast to other thrombopoietin receptor (TPO-R, MPL) agonists, EPAG has also been shown in vitro to directly inhibit cell growth of leukemic cells while the underlying mechanisms are still under investigation. 5,6 There is still no formal proof of that observation in patients.…”
mentioning
confidence: 99%